Analisis Kualitas Visual Arsitektur Bioklimatik pada Rumah Gadang di Sumatera Barat - Fahriansyah, Rahmadatul; Nugroho, Agung Murti (Jurnal Mahasiswa Departemen Arsitektur, 2025)
Modernization has led to the gradual abandonment of Rumah Gadang, the vernacular architecture of the Minangkabau people, in favor of modern residential buildings that often neglect bioclimatic principles necessary for achieving passive thermal comfort and energy efficiency. This study addresses this issue with the aim of inspiring modern architectural design by analyzing the application of bioclimatic principles in two Rumah Gadang located in the Seribu Rumah Gadang area, Solok Selatan. A qualitative approach was employed through direct observation, visual documentation, and literature review. The findings provide a fundamental understanding of how physical elements of Rumah Gadang contribute to natural thermal comfort, particularly through passive strategies such as high-pitched roofs with spacious cavities, wooden walls, continuous overhangs and window openings, and raised floors that facilitate air circulation. However, both case studies revealed a lack of vegetated landscaping, which could be improved to enhance environmental performance. From a multidisciplinary perspective, this research underscores the importance of preserving local architecture as a reference for climate-adaptive design while simultaneously serving as a culturally contextual and sustainable architectural expression.